Freeing Animals: Sino-Tibetan Buddhist Environmentalism and Ecological Challenges - Yu, Dan (Religions, 2023)
Buddhist environmentalism in its varieties across the world is an integral part of the global environmental discourse centered on exploring new planetary ethics for sustainable futures. While recognizing the Buddhist role in global environmental movements, the author of this article proposes that the observable strength of Buddhist environmentalism is in local and global environmental advocacy grounded in the Buddhist ethics of interdependence, even as, canonically, Buddhism does not offer what is commonly recognized by scientists and scholars as traditional ecological knowledge or religious ecology. To substantiate this, this article offers a textual assessment of the Buddhist canon’s lack of systematic ecological knowledge, and a case study of how freeing domestic animals and advocating vegetarianism among contemporary Tibetan Buddhists in China, inclusive of non-Tibetan converts, mainly benefits human wellbeing and at the same time is entangled in social affairs that have little to do with the ecological wellbeing of the Tibetan Plateau and urban China. This debate is by no means intended to negate the successes of Buddhist environmentalism; instead, it draws fine lines between the claimed canonic basis of Buddhist ecology, the strength of Buddhist environmental advocacy, the everyday practices of Buddhism, and the aspirations for strengthening the ecological foundation of Buddhist environmental activism. Thinking in line with eco-Buddhists, the author concludes the article by proposing an Earth Sutra, a hypothetical future canonic text as the ecological basis of Buddhist environmentalism.